1974
DOI: 10.1111/j.1365-2621.1974.tb17985.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenderization of Meat With Papaya Latex Proteases

Abstract: S Tenderization of meat by papaya latex preparations was achieved by the combined action of several proteases. Both in vitro and in vivo application of enzymes gave degradation of muscle proteins, and degradation of connective tissue only after heat denaturation. Purified papaya enzymes‐papain, chymopapain and papaya peptidase A‐were uniformly distributed throughout the various muscles and in the extravascular system after antemortem injection into the vascular system. Chymopapain was the primary contributor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
20
1
1
Order By: Relevance
“…Actinidin can have applications in the food industry replacing other plant sulfhydryl proteases like papain and ficin, used as meat tenderizers (Kang and Warner, 1974;Wada et al, 2002), removers of chill haze in beer (Wallerstein, 1911), improvers in the processing quality of cereals (Feldberg and Baker, 1971), as well as plant milk clotting enzymes for novel dairy products (Lartigue, 1975;Mustafa et al, 1990;Fadyloglu, 2000). It has been reported that dairy products clotted with the use of kiwi juice actinidin develop less off-flavor notes that are attributed to bitter peptides occurring when ficin and papain are used in the same products (Saha and Hayashi, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Actinidin can have applications in the food industry replacing other plant sulfhydryl proteases like papain and ficin, used as meat tenderizers (Kang and Warner, 1974;Wada et al, 2002), removers of chill haze in beer (Wallerstein, 1911), improvers in the processing quality of cereals (Feldberg and Baker, 1971), as well as plant milk clotting enzymes for novel dairy products (Lartigue, 1975;Mustafa et al, 1990;Fadyloglu, 2000). It has been reported that dairy products clotted with the use of kiwi juice actinidin develop less off-flavor notes that are attributed to bitter peptides occurring when ficin and papain are used in the same products (Saha and Hayashi, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, in many cases, it is desirable to artificially induce tenderization by applying exogenous enzymes to attain certain quality attributes (Muller 1995). Proteolytic enzymes of plant origin have been extensively studied and used for beef tenderization (Kang and Warner 1974; Foda 1976; Richardson 1977; Alder‐Nissen 1986; Muller 1995; Aishma and others 1996). Ficin, the sulfhydryl protease of the fig tree ( Ficus carica ) is reported to hydrolyze and increase solubility of muscle proteins and its application for beef tenderization has been suggested (El‐Gharabi and Whitaker 1962; Uhlig 1998; Matilus and others 1999; Ramezani and others 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is used as a general non-speciÐc proteinase for meat tenderisation, removal of chill haze in beer and improvement in the processing quality of cereals (Wallerstein 1911 ;Feldberg and Baker 1971 ;Kang and Warner 1974).…”
Section: Introductionmentioning
confidence: 99%